Optimization of the Structural Parameters of Fisheye Contact Pairs by RSM - Xiao, Maohua; Guo, Jun; Lu, Xinhua; Shi, Liping; Zhang, Jing; Lin, Hong (Manufacturing Technology Journal, 2019)
Fisheye contact pair is an important component of board level interconnection products wide range of applications. However, insertion and withdrawal force have great influence on the contact deformation due to their small size and complex structure. In this paper to the fisheye contact pairs of interconnection products as the research object, the main parameters were analyzed which could affect the contact deformation of fisheye structure, and factor analysis of them were performed. And three relatively more significant factors were extracted. The simulation based on Response Surface Methodology (RSM) is designed, And the experimental data was conducted regression fitting, getting the second regression model. The established quadratic regression model was analyzed based on MATLAB and the response of various factors on the insertion and withdrawal force, then the optimized parameter model of fisheye structure was obtained. The research shows that the quadratic regression model based on response surface methodology fitting accuracy was high and there were good practical value about it.
Keywords: Fisheye contact pair; Structural parameters; RSM; MATLAB; Design optimizing